2021
DOI: 10.9734/jpri/2021/v33i52b33623
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Effectiveness of Therapeutic Measures for Generalized Periodontitis in Patients with Hypertension

Abstract: The program of standard therapeutic measures in 45 patients with Generalized Chronic Periodontitis (GCP) and background hypertension, group I(a), included hirudotherapy, for comparison, the effectiveness of traditional treatment was evaluated in 40 patients, group I(b), who refused to use medical leeches. In the second comparison group (35 patients), patients with GCP, but normal blood pressure, also received only a set of traditional methods of treatment. The inclusion of hirudotherapy in the program of thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Majority of the studies have confirmed that diabetes has a significant risk factor for causing periodontitis. But periodontitis in correlation with diabetes was more commonly seen in male which was contradictory [38].…”
Section: Discussionmentioning
confidence: 98%
“…Majority of the studies have confirmed that diabetes has a significant risk factor for causing periodontitis. But periodontitis in correlation with diabetes was more commonly seen in male which was contradictory [38].…”
Section: Discussionmentioning
confidence: 98%